Computer program of nutrition assessment for elderly dietary planning by using food exchangelist / Achara Dholvitayakhun ... [et al.] - Dholvitayakhun, Achara; Kaewwongkhieo, Kriangkrai; Kluabwang, Jukkrit (2018)
Statistics in Thailand show that the elderly population aged over 60 years will increase continuously, from 13.2 percent in 2010 to 32.1 percent in 2040. In addition, over 80% of the elderly suffer at least one chronic condition, and 50% have at least two. The situation of elderly people is leading to rising progressively cost of caring and threatens the economic well-being of many nations around the world. Nutrition has been recognized as an important factor in influencing the functional outcome of aging. Therefore, it is extremely important to develop adequate and helpful means to assist the elderly inself-controlling their nutritional state while healthy, and when managing chronic diseases such as diabetes and hypertension. Energy balance method associated with food exchange list is the commonly used method to solve the dietary planning problem, elderly case also use this method as well. Usually, the energy balance method’s solutions can be obtained by trial and error approach or experience-dependent approach, such that it may inconvenient for elderly taking care themselves. This research proposed an alternative finding proper solutions of the elderly dietary planning problem by using an efficient iterative computation. The proposed method was coded in PHP language due to it is familiar with social network. The computational results from five males and five female elderly samples show that their all solutions met all constrains within a few milliseconds by a notebook. The performance of the proposed method is satisfied our basic requirements and will be extended to further challenges.